Indian pigment paintings on cloth - Talwar, Kay (Historic textiles of India at the Calico Museum, Ahmedabad, 1979)
On the temple hangings of the Vallabhacharya sect, Jain patas, phadas and panchangas of western India, Orissa patachitras, cloth paintings of Nepal, and other regional styles; includes an annotated catalog of the Museum's collection.